Upaya Guru Pendidikan Agama Islam Dalam Meningkatkan Self Control Siswa - rahmawati Cahyaningrum; Joko Sarjono; Muin Abdullah (Sekolah Tinggi Agama Islam Raudhatul Ulum, 2023)
This study aims to reveal how the efforts of Islamic religious education teachers in increasing self control in SMP Muhammadiyah 6 Surakarta students. This type of research used is qualitative. The results of the research and discussion show that the efforts of Islamic religious education teachers in increasing self-control can be seen from three aspects of self-control, namely: first, cognitive control is carried out through active learning. Second, behavior control carried out by religious activities at SMP Muhammadiyah 6 Surakarta has a major influence on the process of forming children's character, especially in terms of behavior. Third, decision control is carried out through religion in which there are religious values that guide students in gaining insight in the form of self control. The inhibiting factors in increasing self-control in students are the nature of students who are brought from home, behaviors that students get from the surrounding environment such as family and friendship, and economic factors.